Live imaging and quantitative analysis of Aspergillus fumigatus growth and morphology during inter-microbial interaction with Pseudomonas aeruginosa - Sebastian Wurster (Taylor & Francis Group, 2020)
Pseudomonas aeruginosa (PA) and Aspergillus fumigatus (AF) chronically colonize the airways of patients with cystic fibrosis or chronic immunosuppression and mutually affect each other’s pathogenesis. Here, we evaluated IncuCyte time-lapse imaging and NeuroTrackTM (NT) analysis (Wurster et al., 2019, mBio) as a toolbox to study mycelial expansion and morphogenesis of AF during interaction with PA. Co-incubation of AF with supernatant filtrates of wild-type (WT) PA strains strongly inhibited hyphal growth and branching. Consonant with prior metabolic studies, pyoverdine-deficient PA mutants had significantly attenuated inhibitory capacity. Accordingly, purified PA products pyoverdine and pyocyanin suppressed mycelial expansion of AF in a concentration-dependent way. Using fluorescence-guided tracking of GFP-AF293 mycelia during co-culture with live WT PA cells, we found significant inoculum-dependent mycelial growth inhibition and robust precision of the NT algorithm. Collectively, our experiments position IncuCyte NT as an efficient platform for longitudinal analysis of fungal growth and morphogenesis during bacterial co-infection.